Comparative evaluation of organomineral fertilizer and NPK 151515 on growyh and yield of cassava varieties in Ibadan, southwestern Nigeria - Edet, M.A.; Tijani-Eniola, H.; Okechukwu, R.U. (2013)
Field experiments were conducted at Ajibode area in Ibadan to investigate the effects of organomineral fertilizer (OF) and NPK fertilizer treatments on the growth and yield of two cassava varieties: TMS 30572 and TMS 92/0326. Five rates of OF (1.5, 2.5, 3.5, 4.5, 6.0 t/ha), NPK 15:15:15 at 600 kg/ha and control (no fertilizer) treatments (subplots) were valuated on cassava (main plot) which was planted at 10,000 plants per hectare. Treatments were assigned using a split plot arrangement in a randomized complete block design with three replicates. Parameters assessed include plant height, number of leaves, leaf area index (LAI) fresh and dry root yield (DRY). Data were analyzed using ANOVA at p < 0.05. Mean LAI at 6 MAP (2.86 and 2.21), fresh and DRY (at harvest) of 32.2 and 12.3 t/ha obtained for TMS 92/0326 were significantly higher than that of TMS 30572 (26.6 and 9.5t/ha), respectively. Fresh root yields at 12 MAP harvest obtained with various fertilizer treatments were in the order: 35.3 > 33.0 > 32.5 > 31.2 > 30.9 > 26.1 > 20.2 t/ha for 6.0 t OF/ha, NPK at 600 kg\ha, 4.5, 2.5, 3.5, 1.5 t OF/ha and control, respectively. Optimum yield of cassava root was obtained with application of 2.5 t OF/ha, similar to that obtained in NPK treatment, thus making OF a good substitute for mineral fertilizer.